Effects of straw returning on functional genes and functional groups of soil microorganisms - WANG Binhao; WU Yuping; CHEN Yanbo; ZHANG Fangzhou; LIU Zhenyu; ZHANG Shuo; WANG Xianting (浙江大学学报. 农业与生命科学版, 2024)
Sustainable straw utilization is an important measure for accelerating the green and low-carbon development of agriculture. However, there is relatively little research on the comprehensive impact of straw returning on soil ecological health from the perspectives of microbial communities and functions within the framework of soil “One Health”. To address this gap, soil samples were collected from paddy fields in Ningbo City of Zhejiang Province, where straw has been returned for a long time (5 years or more), and high-throughput metagenomic sequencing was performed to understand the effects of straw returning on antibiotic resistance genes (ARGs), methane-cycling genes (MCGs), nitrogen-cycling genes (NCGs), virulence factor genes (VFGs), and their host taxa. The results showed that long-term straw returning affected the diversity of ARGs, MCGs, NCGs, and VFGs in the soil, with significantly decreased richness of NCGs and VFGs, as well as nitrogen-cycling taxa. Long-term straw returning also reduced the abundance of the key methanogenesis genes mcrA, B, C, and G and the methanogenesis taxon Methanosarcina mazei. It also significantly reduced the abundance of genes related to methylotrophic methanogenesis. Moreover, the abundance of VFGs significantly increased under long-term straw returning. In addition, the abundance ratio of the functional genes mcrA and pmoA, as well as that of norB and nosZ, was significantly reduced, which suggested that more CH4 and N2O in rice fields under straw returning will be converted. Multiple regression on distance matrix analysis showed that total organic carbon and dissolved organic carbon were closely related to the soil microbial functional group composition (P＜0.05). In summary, long-term straw returning increases the risk of rice diseases and may also reduce emission rates of greenhouse gases, such as CH4 and N2O.